PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MIND MAP DI KELAS VI SD NEGERI 15 KAPALOKOTO KECAMATAN SUNGAIPUA - Ricky Gustiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is included in classroom action research. The purpose of this study is to improve the process and learning outcomes of social studies by using indmap in students of SD Negeri 15 Kapalokoto, Sungaipua District. Using the Mind Map method in class VI SDN 15 Kapalokoto, Sungaipua District. from the average grade point of 65.76 to 71.92 and when viewed from the achievement of KKM this value has reached KKM. Then in cycle II, the average score of students increased again to 76.90. The score has reached KKM and has reached the target where more than 75% of students obtained scores of more than 70.00. The results of observing student attitudes, from cycle I to cycle II have increased. This is evidenced by increased student learning outcomes. From the description above, it can be concluded that the learning outcomes and activeness of grade VI students of SD Negeri 15 Kapalokoto, Sungaipua District increased by using Minmap in social studies subjects.